Method for synergistically enhancing strength and plasticity of additive manufacturing titanium alloy through Si and Fe
By introducing Si and Fe into additively manufactured titanium alloys, refine the grains and stabilize the β phase, the problems of coarse structure and poor strong plasticity of the titanium alloy are solved, the tensile strength and elongation of fracture are improved, and the strong Plastic matching.
Patent Information
- Application Number
- CN202411729696.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The titanium alloy has thick structure and poor strong plasticity, and traditional methods are difficult to effectively solve by component design.
Si and Fe are introduced in additive manufacturing titanium alloys, and the primary β grains and martensite sheets are refined using Si's growth restriction factor, and the β phase is stabilized by Fe, and material deformation is coordinated to achieve fine crystal strengthening and solid solution strengthening.
Through the synergistic action of Si and Fe, the tensile strength and elongation of fracture of titanium alloys are significantly improved, strong plastic matching is improved, and the risk of brittle silicide precipitation during high-temperature applications is reduced.
Smart Images

Figure CN119457114A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for synergistically enhancing the strength and plasticity of an additively manufactured titanium alloy using Si and Fe, and belongs to the technical field of metal preparation. Background Art
[0002] Titanium alloys have been widely used in aerospace, chemical engineering, marine engineering, medical equipment and other fields due to their high specific strength, excellent fatigue resistance, outstanding corrosion resistance and oxidation resistance, as well as excellent damage tolerance. Despite these advantages, titanium alloys have low thermal conductivity, high deformation resistance and narrow forging temperature range, which pose major challenges to the manufacture of complex parts. These characteristics may make it difficult to form parts with complex shapes and increase manufacturing costs. Additive manufacturing technology, with its high material utilization rate and forming capabilities that are not limited by part shape and size, not only effectively overcomes these technical bottlenecks, but also achieves lightweight, high performance and low cost of parts.
[0003] Titanium alloy additive manufacturing technology is gradually maturing, but there are still some common problems. In the traditional titanium alloy printing process, coarse columnar crystals will be formed, resulting in anisotropy of mechanical properties, which is not conducive to application. At the same time, the coarse structure is not conducive to obtaining high mechanical properties (fine grain strengthening). The printed titanium alloy structure is mostly coarse martensite, which has high strength but poor plasticity (low elongation). Subsequent heat treatment is required to partially decompose or completely eliminate the martensite to improve plasticity, but this comes at the cost of strength loss, and also increases production processes and costs.
[0004] Taking Ti6Al4V alloy, which is currently the most widely used alloy, as an example, the main solution is to introduce alloying elements to suppress the formation of columnar crystals by strengthening the supercooling of the components, thereby achieving a fine equiaxed crystal structure. These elements include Fe, Co, Cu, Mo, etc. The effectiveness of this method has been verified by a large number of experiments. Si is a eutectic β-stabilizing element, which theoretically also has the effect of eliminating columnar crystals and refining grains. Studies on traditional cast / forged titanium alloys have confirmed that Si easily reacts with titanium to form brittle titanium-silicon compounds, which will lead to a decrease in the plasticity of titanium alloys. Therefore, the introduction of Si is usually avoided in titanium alloys, and even if it is introduced, it is lower than the solubility (0.4 wt%), so the Si in titanium alloys is lower than this theoretical value. Additive manufacturing titanium alloys themselves have the problem of poor plasticity, so Si is not considered to be an effective element to improve the performance of additive manufacturing titanium alloys. The key to improving the performance of additive manufacturing titanium alloys with Si elements is to ensure that Si exists in the form of solid solution and does not form titanium-silicon compounds. In addition, supersaturated Si also has a limit, and the higher the degree of Si supersaturation, the higher the risk of brittle silicide precipitation when used at high temperatures, but low Si supersaturation is not conducive to obtaining higher strength and plasticity. As for the problem of printed titanium alloy structure being martensite, there is currently no effective method to solve it through composition design except heat treatment and control of printing process. Summary of the invention
[0005] The purpose of the present invention is to provide a method for synergistically enhancing the strength and plasticity of additively manufactured titanium alloys with Si and Fe in order to address the problem that the current additively manufactured titanium alloys have coarse structures and poor strength and plasticity. This method introduces Si and Fe into the additively manufactured titanium alloy, utilizes the extremely high growth restriction factor of the Si element to refine the primary β grains and martensite lamellae, and utilizes the characteristics of the high cooling rate of additive manufacturing to dissolve the supersaturated silicon in the titanium alloy, thereby achieving extremely high grain refinement and solid solution strengthening effects; in addition, the β-strong stabilizing element Fe is used to stabilize the β phase, and the deformation of the material is coordinated by increasing the β phase content, thereby achieving excellent strength and plasticity matching of the material. The present invention achieves an improvement in strength and plasticity, wherein Si exists in the form of a solid solution and does not form brittle silicides.
[0006] The technical solution of the present invention is: A method for synergistically enhancing the strength and plasticity of an additively manufactured titanium alloy using Si and Fe, comprising the following steps: (1) Preparation of mixed powder The silicon source powder, titanium source powder and iron source powder are mixed to obtain a mixed powder. The target component mass is calculated based on the sum of the mass of Si, Fe and Ti in the mixed powder. The mass of silicon is 0.4% to 3% of the target component mass, and the mass of iron is 0.01% to 4% of the target component mass. The silicon source is pure silicon powder, SiO2, SiC or silicon-titanium master alloy (TixSiy); The iron source is pure iron, iron oxide or titanium-iron master alloy (TixFey); The titanium source is pure titanium or a titanium alloy; the titanium alloy is specifically α titanium alloy, β titanium alloy or α+β titanium alloy; Preferred are Ti6Al4V, TA7 or Ti1023.
[0007] (2) Ball milling of mixed powder The prepared mixed powder is ball-milled under argon protection, and the ball-milling parameters are as follows: ball-to-material ratio 2:1-15:1, rotation speed 100-500 rpm, and ball-milling time 0.5-6 hours; (3) Molding process The mixed powder after ball milling is subjected to a molding process to obtain a titanium alloy block.
[0008] The molding process described is additive manufacturing, specifically direct laser energy deposition or laser powder bed fusion.
[0009] When direct laser deposition technology is used, the following steps are included: laser power is 600-1500 W, single track width is 1.5-3 mm, track spacing is 0.9-1.8, scanning speed is 5-15 mm / s, and each layer is alternated by 0-90°.
[0010] When the laser powder bed melting technology is used, the following steps are included: the laser power is 100-500 W, the scanning speed is 1000-2000 mm / s, the rotation angle between each layer is 20-90°, and the layer thickness is 0.3-0.8 mm.
[0011] The essential features of the present invention are: Due to the high cooling rates and high thermal gradients inherent in metal additive manufacturing processes, especially titanium alloys, which usually lead to high-density micron-sized martensite and almost entirely columnar grains, resulting in a serious mismatch between the strength and plasticity of deposited titanium alloys, some early additive manufacturing work has reported the addition of different elements (such as B, O, Mo, and Cu, etc.) to achieve grain refinement. Si is not considered to be an effective additive for improving the strength and plasticity of additively manufactured titanium alloys due to its low solid solubility and easy formation of brittle silicides. However, the higher the degree of supersaturation of Si, the higher the risk of brittle silicide precipitation during high-temperature applications.
[0012] The present invention introduces Si with a low supersaturation degree (for example, from 3.5 times of the control sample to 2 times of the solid solubility of Example 1), and introduces Fe at the same time, and utilizes the synergistic effect of the two to improve strength and plasticity, which not only reduces the risk of supersaturated silicon precipitation to form brittle silicides, but also can achieve a better strength and plasticity improvement effect than high supersaturation Si, and the present invention does not require heat treatment. Therefore, the design concept of the present invention is to utilize the synergistic effect of supersaturated Si and solid solution Fe to achieve the improvement of strength and plasticity of additively manufactured titanium alloys through solid solution strengthening, fine grain strengthening and phase ratio control.
[0013] The beneficial effects of the present invention are: Ideal metal structural materials maintain good plasticity and toughness while maintaining high strength, but the strength and plasticity of the material show a significant inverse relationship, that is, the strength increases while the plasticity and toughness decrease. Taking the most typical Ti6Al4V alloy as an example, the introduction of 1.25wt% supersaturated Si (3.5 times the solid solubility) increases the strength from 1110 MPa to 1407 MPa, and the elongation increases to 9.61%. By introducing 0.75 wt% Si (2 times the solid solubility) and 0.75 wt% Fe in the present invention, the tensile strength is further increased to 1454 MPa, and the elongation at break is further increased to 10.66% (Example 1), that is, the strong plasticity is further improved. In addition, due to the reduction in Si content, the risk of brittle silicide precipitation during high temperature applications is reduced (reduced by 40%). BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is the optical microscopic grain image of Example 1, Example 2 and Ti6Al4V prepared by the same process.
[0015] Figure 2 Transmission electron microscope morphology images of Example 1, Example 2 and Ti6Al4V prepared by the same process.
[0016] Figure 3 XRD diagrams of Example 1, Example 2 and Ti6Al4V prepared by the same process.
[0017] Figure 4 This is the energy spectrum element analysis diagram of Example 1.
[0018] Figure 5 The stress-strain curves of Example 1, Example 2, Ti6Al4V prepared by the same process, and Ti6Al4V+1.25 wt%Si.
[0019] Figure 6 These are actual pictures of the titanium alloys of Examples 1 and 2. DETAILED DESCRIPTION
[0020] The present invention will be further described below in conjunction with embodiments.
[0021] The present invention aims at the coarse structure and poor strength and plasticity of additively manufactured titanium alloys, and provides a method for improving the strength and plasticity of additively manufactured titanium alloys by utilizing the synergistic effect of Si and Fe. Its mechanism of action: ① Utilize Si and Fe to increase the composition supercooling of the molten pool to achieve the transformation from columnar crystals to equiaxed crystals and refine the structure; ② Supersaturated Si and dissolved Fe can play a significant role in solid solution strengthening; ③ The introduction of Fe will increase the proportion of β phase in the alloy, which is more conducive to coordinated deformation. First, the technical route of the present invention is explained.
[0022] (1) Preparation of mixed powder The silicon source powder, titanium source powder and iron source powder are mixed to obtain a mixed powder. The target component mass is calculated based on the sum of the mass of Si, Fe and Ti in the mixed powder. The mass of silicon is 0.4% to 3% of the target component mass, and the mass of iron is 0.01% to 4% of the target component mass. The silicon source is pure silicon powder, SiO2, SiC or silicon-titanium master alloy (TixSiy); The iron source is pure iron, iron oxide or titanium-iron master alloy (TixFey); The titanium source is pure titanium or a titanium alloy; the titanium alloy is specifically α titanium alloy, β titanium alloy or α+β titanium alloy; Preferred are Ti6Al4V, TA7 or Ti1023.
[0023] (2) Ball milling of mixed powder The prepared mixed powder is ball-milled under argon protection, and the ball-milling parameters are as follows: ball-to-material ratio 2:1-15:1, rotation speed 100-500 rpm, and ball-milling time 0.5-6 hours; (3) Molding process The mixed powder after ball milling is subjected to a molding process to obtain a titanium alloy block; The molding process described is additive manufacturing, such as direct laser energy deposition, laser powder bed fusion, etc.; Here we choose direct laser deposition technology in additive manufacturing process for illustration. Direct laser deposition technology: laser power is 600-1500 W, single track width is 1.5-3 mm, track spacing is 0.9-1.8, scanning speed is 5-15 mm / s, and each layer alternates 0-90°.
[0024] When using laser powder bed fusion technology, the following steps are included: laser power is 100~500 W, scanning speed is 1000~2000 mm / s, rotation angle between layers is 20~90°, and layer thickness is 0.3~0.8 mm.
[0025] The purity of the silicon powder and iron powder is greater than 99%, and the Ti6Al4V titanium alloy powder is a conventional powder for commercial additive manufacturing.
[0026] The present invention is further described below in conjunction with embodiments. Example 1 Weigh 1.5 g silicon powder, 1.5 g iron powder, and 197 g Ti6Al4V titanium alloy powder (containing 177.3 g titanium) and place them in a 500 ml stainless steel ball mill jar filled with argon. Use a planetary ball mill at 350 rpm for 2 hours, with a ball-to-material ratio of 2.5:1.
[0027] The mixed powder after ball milling was taken out and the sample was prepared by direct laser energy deposition process, with laser power of 900W, scanning speed of 10 mm / s, alternating 90° between layers, powder feeding speed of 3 g / min, single track width of 2 mm, and track spacing of 1.2 mm. The Si and Fe synergistically reinforced Ti6Al4V sample with a length of 80 mm, a width of 30 mm, and a height of 20 mm was obtained. (Among them, the sum of the masses of the three elements Si, Fe and Ti in the alloy is taken as the target component mass, the mass of silicon is 0.83% of the target component mass, and the mass of iron is 0.83% of the target component mass) Example 2 Weigh 2.2 g silicon powder, 2.2 g iron powder, and 195.6 g Ti6Al4V titanium alloy powder (containing 176.04 g titanium) and place them in a 500 ml stainless steel ball mill and fill it with argon. Use a planetary ball mill at 350 rpm for 2 hours, with a ball-to-material ratio of 2.5:1. Take out the mixed powder after ball milling and use direct laser energy deposition technology for sample preparation, with a laser power of 900 W, a scanning speed of 10 mm / s, alternating 90° between layers, a powder feeding speed of 3 g / min, a single channel width of 2 mm, and a channel spacing of 1.2 mm. A Si and Fe synergistically reinforced Ti6Al4V sample with a length of 80 mm, a width of 30 mm, and a height of 20 mm is obtained.
[0028] Example 3 Weigh 1.5 g silicon powder, 1.5 g iron powder, 197 g Ti6Al4V titanium alloy powder (containing 177.75 g titanium), place in a 500 ml stainless steel ball mill, and fill with argon. Use a planetary ball mill at 350 rpm for 2 hours, with a ball-to-material ratio of 2.5:1. Take out the mixed powder after ball milling, and use laser powder bed melting technology for sample preparation, with a laser power of 350 W, a scanning speed of 1200 mm / s, a rotation angle of 60° between each layer, and a layer thickness of 0.4 mm. Obtain a supersaturated Si and Fe synergistically enhanced Ti6Al4V sample with a length of 80 mm, a width of 10 mm, and a height of 10 mm. The effect is similar to that of Example 1.
[0029] The optical microscope test results of the Ti6Al4V sample prepared by the additive manufacturing process and the Si and Fe synergistically reinforced Ti6Al4V sample in Example 1 are as follows: Figure 1 As shown in the figure, the Ti6Al4V alloy presents columnar grains, while the alloy of Example 1 presents fine equiaxed grains. Further increasing the content of Si and Fe (Example 2) further refines the grains, indicating that the addition of Si and Fe can inhibit the formation of columnar crystals and achieve the effect of refining grains, which is one of the reasons for improving the strength and plasticity of titanium alloys at the same time. Figure 2 This is the transmission electron microscope morphology of nano-martensite in the titanium alloy of Example 1. The width of martensite is less than about 200 nm, which is another reason for the simultaneous improvement of the strength and plasticity of the titanium alloy.
[0030] Figure 3 The XRD spectrum of the titanium alloy of Example 1. Phase calculation using XRD found that the volume fraction of the β phase can be significantly increased after the addition of Fe. The β phase, as a tough phase in the titanium alloy, can coordinate plastic deformation, thereby improving the plasticity of the material.
[0031] Figure 4 This is the micro-area energy spectrum of the titanium alloy of Example 1. The results show that Si is evenly distributed in the matrix without silicide, which has the effect of solid solution strengthening, while Fe is segregated in the β phase.
[0032] The tensile test results of Example 1 are as follows Figure 5 As shown in the figure (the test is based on GB / T228.1-2021), it can be seen from the figure that compared with the Ti6Al4V alloy prepared by the same process, the total strength and plasticity of the titanium alloy of Example 1 are significantly improved. Compared with the sample of Example 1, the Ti6Al4V alloy prepared by the same process has lower strength than the sample of Example 1 due to the coarse columnar grains and micron-sized martensite. The sample of Example 1 has excellent strength-plastic matching due to the synergistic strengthening effect of fine equiaxed crystals and nano-martensite, the solid solution strengthening effect of Si, and the back stress strengthening effect caused by Fe.
[0033] Figure 6 The physical image of the printed sample shows that the sample has high shape stability and good surface quality, which is beneficial for the preparation of complex structural parts.
[0034] Titanium alloys have high specific strength, excellent fatigue resistance, outstanding corrosion resistance and oxidation resistance, but there is a problem of difficult processing. Additive manufacturing technology can effectively reduce the production cost and manufacturing cycle of complex titanium alloy parts, but the titanium alloys manufactured by additive manufacturing have problems of coarse structure and poor strength and plasticity. Taking the most common Ti6Al4V alloy as an example, the tensile strength of the alloy can be increased from 1110MPa to 1454MPa, and the elongation at break can be increased from 7.26% to 10.66% through the present invention. A method of synergistically enhancing the strength and plasticity of titanium alloys manufactured by additive manufacturing of Si and Fe of the present invention can effectively solve the bottlenecks and problems of coarse structure and low strength and plasticity of titanium alloys manufactured by additive manufacturing, and is expected to be applied in the fields of aerospace and military equipment.
[0035] Matters not covered by the present invention are known technologies.
Claims
1. A method for synergistically enhancing the strength and plasticity of titanium alloys manufactured by additive manufacturing using Si and Fe, characterized in that the method comprises the following steps: (1) Preparation of mixed powder The silicon source powder, titanium source powder and iron source powder are mixed to obtain a mixed powder. The target component mass is calculated based on the sum of the mass of Si, Fe and Ti in the mixed powder. The mass of silicon is 0.4% to 3% of the target component mass, and the mass of iron is 0.01% to 4% of the target component mass. The silicon source is pure silicon powder, SiO2, SiC or silicon-titanium master alloy; The iron source is pure iron, iron oxide or titanium-iron master alloy; The titanium source is pure titanium or a titanium alloy; the titanium alloy is specifically α titanium alloy, β titanium alloy or α+β titanium alloy; (2) Ball milling of mixed powder The prepared mixed powder is ball-milled under argon protection, and the ball-milling parameters are as follows: ball-to-material ratio 2:1-15:1, rotation speed 100-500 rpm, and ball-milling time 0.5-6 hours; (3) Molding process The mixed powder after ball milling is subjected to a molding process to obtain a titanium alloy block; The molding process described is additive manufacturing.
2. The method for synergistically enhancing the strength and plasticity of titanium alloys in additive manufacturing by Si and Fe as described in claim 1, characterized in that the titanium alloy is TA7, Ti1023 or Ti6Al4V.
3. The method for synergistically enhancing the strength and plasticity of titanium alloys in additive manufacturing using Si and Fe as described in claim 1, characterized in that the molding process is direct laser energy deposition or laser powder bed melting.
4. The method for synergistically enhancing the strength and plasticity of titanium alloys manufactured by additive manufacturing of Si and Fe as claimed in claim 1, characterized in that when it is a direct laser deposition technology, it comprises the following steps: the laser power is 600-1500 W, the single track width is 1.5-3 mm, the track spacing is 0.9-1.8, the scanning speed is 5-15 mm / s, and the layers are alternated by 0-90°; When the laser powder bed melting technology is used, the following steps are included: the laser power is 100-500 W, the scanning speed is 1000-2000 mm / s, the rotation angle between each layer is 20-90°, and the layer thickness is 0.3-0.8 mm.
Citation Information
Patent Citations
Ti-Al-V-Ta double-phase titanium alloy suitable for additive manufacturing
CN114507796A
Titanium alloy suitable for additive manufacturing
CN115044802A
Efficient laser additive manufacturing titanium alloy and heat treatment method for improving anisotropy of titanium alloy
CN115609007A
Resource saving-type titanium alloy member possessing improved strength and toughness and method for manufacturing the same
US20150191812A1